Microbial numbers and enzymatic activities in agricultural soils and their variations during storage - Lysková, Petra (Univerzita Pardubice, 2009)
The manipulation of soil microbial communities using soil and crop management practices is a basic strategy in the development of stable agricultural systems. Such systems are based, in part, on the efficient management of soil microorganisms to improve soil quality. Microbial numbers and enzymatic activities in agricultural soils that differed in fertilization practice, method and intensity of tillage, and crop rotation were investigated. Agricultural soils showed significant differences in some of physical-chemical properties (phosphorus content, available Ca) between the two cropping systems tested. Microbial counts as well as enzyme activities of the site with crop rotation were higher than in the soil under many years of continuous banana cultivation. The decrease in microbial activity of tested soils after the storage for 30 and 60 days at room temperature indicates that the selected temperature is not suitable for storage, even for the short periods.